Separation of metabolic products by electroosmotic dialysis in the plasma model. (20th December 2017) - Lenninger, M.; Schweibert, N.; Leierer, J.; Weigel, G.; Loacker, L.; Neuwirth, H.; Mayer, G.; Bechtold, T.
Abstract: Hemodialytic membrane separation of low molecular weight solutes e.g. urea and creatinine bases on diffusion processes generated by the respective concentration gradient between dialysate and blood plasma. Electroosmotic drag of liquid through membranes offers a new transport concept for separation of metabolic products in dialysis. In this work electroosmotic drag of membranes made of textile reinforced agar, collagen, bovine pericardium, acrylonitrile/sodium methallylsulfonate copolymer as well as cation exchange membranes was studied using a five chamber electroosmotic cell in continuous operation mode. The textile reinforced agar membrane, the copolymer membrane and the bovine pericard membrane were selected for electroosmotic dialysis experiments using plasma as biological model. Vitamin B12, myoglobin, albumin and beta-2-microglobulin plasma concentrations were monitored to investigate both, membrane permeation of these markers in direction of the electroosmotic flow and possible negative effects of the electroosmotic treatment on protein stability. Transport of low molecular weight substances urea and creatinine into the recipient electrolyte was achieved without permeation of Vitamin B12 and plasma proteins. Coagulation of proteins due to the electrical field applied was not on a significant level. Monitoring of biologically relevant ions Na +, K +, Ca 2+, PO4 3−, Cl − demonstrated that the ion movement in electroosmosis also will permit control of ion concentrations during dialysis. The transported volume of up to 14 ml Ah −1 demonstrates the potential for a significant reduction in dimensions of devices for dialysis, thus offering new aspects for miniaturisation and home dialysis.